Cultivation of Chlorella vulgaris in a pilot-scale sequential-baffled column photobioreactor for biomass and biodiesel production - Lam, M.K. (Elsevier Ltd, 2014)
Pilot-scale cultivation of Chlorella vulgaris in a 100 L sequential baffled photobioreactor was carried out in the present study. The highest biomass yield attained under indoor and outdoor environment was 0.52 g/L and 0.28 g/L, respectively. Although low microalgae biomass yield was attained under outdoor cultivation, however, the overall life cycle energy efficiency ratio was 3.3 times higher than the indoor cultivation. In addition, negative energy balance was observed in producing microalgae biodiesel under both indoor and outdoor cultivation. The minimum production cost of microalgae biodiesel was about RM 237/L (or USD 73.5/L), which was exceptionally high compared to the current petrol diesel price in Malaysia (RM 3.6/L or USD 1.1/L). On the other hand, the estimated production cost of dried microalgae biomass cultivated under outdoor environment was RM 46/kg (or USD 14.3/kg), which was lower than cultivation using chemical fertilizer (RM 111/kg or USD 34.4/kg) and current market price of Chlorella biomass (RM 145/kg or USD 45/kg). Â© 2014 Elsevier Ltd. All rights reserved.